Effects of the Novel Formulated Forms of Curcumin on Tumor Growth Inhibition in Breast Cancer - Milad Hashemzehi; Amir Avan; Maliheh Hasanzadeh; Soodabeh Shahid Sales; Zohreh Yousefi; Sima Kadkhodayan; Marjaneh Farazestanian; Mona Joudi Mashhad; Majid Khazaei; Seyed Mahdi Hassanian (Mashhad University of Medical Sciences, 2018)
Introduction: Breast cancer is the most common malignancy and the second leading cause of death due to cancer in women following lung cancer. Ample evidence has shown the antitumor activities of curcumin in breast cancer in preclinical and clinical trials. The anticancer effects of curcumin include the inhibition of cancer cell formation, angiogenesis, and tumor growth. Due to the low absorption of curcumin in the gastrointestinal tract, as well as its low water solubility, rapid metabolism, and high excretion, curcumin has low bioavailability. Therefore, using formulated curcumin could increase its bioavailability. The present study aimed to evaluate the effects of curcumin and its nano-formulated compositions in the prevention and treatment of breast cancer.   Methods: In this review, data were collected via searching in databases such as PubMed, Scopus, Google Scholar, and Magiran to identify the related English and Persian articles published until 2016 using keywords such as nano-forms, clinical study, cancer, breast, and curcumin. In total, 40 studies were identified and reviewed.   Results: Using formulated curcumin could increase its absorption and bioavailability, while it also enhances its effects on cancer cells, including breast cancer cells. Therefore, nano-formulated curcumin was observed to be effective in the prevention and treatment of breast cancer.   Conclusion: Considering the higher bioavailability of the formulated compounds of curcumin compared to its free form and the low toxicity of this herbal medicine, curcumin could be used in combination with other anticancer medications in the treatment of breast cancer.